DAMPAK PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPS - Rahmania Nur; Alresty Sampe Londong; Hasni; Ahmad Syawaluddin (STKIP Subang, 2026)
Impact of the use of Artificial Intelligence (AI) on students' critical thinking skills in social studies lessons. Critical thinking skills have a very strategic position in the social studies learning process. Because this subject not only requires mastery of social and historical facts, but also the ability to analyze social phenomena, evaluate public policies, understand diverse perspectives, and make decisions based on rational and evidence-based arguments. The existence of AI in social studies learning can help to analyze population data, map economic dynamics, simulate social conflicts or evaluate data-driven public policies, all of which have the potential to strengthen students' analysis and evaluation skills. This study aims to determine the model of the implementation model of the effective use of Artificial Intelligence (AI) in social studies learning and the impact of the implementation of the use of Artificial Intelligence (AI) in social studies learning on students' critical thinking skills. This research uses a qualitative method with a literature study approach. The results of the literature study found that the effective AI Implementation Model in social studies learning is a model that places AI as a cognitive tool, not as a substitute for students' thinking processes. As well as the impact of AI on students' critical thinking skills in social studies learning, it shows that positive impacts can help in understanding social phenomena critically, reflectively and data-based. However, it can have a negative impact if the dependence on using AI.